Waduk Universitas Riau Sebagai Ruang Sosial Mahasiswa dan Komunitas Lokal - Annisa; Yumi Andani; Astri Hazizah; Megi Wahyudi; Rafli Hidayat (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
This study aims to analyze the utilization of the University of Riau Reservoir as a social space for students and local communities and to understand the role of the aquatic environment in supporting social activities. The research employed a qualitative approach with a phenomenological design. Data were collected through interviews, observations, and documentation involving University of Riau students and local residents who use the reservoir area. Informants were selected using purposive sampling techniques. Data analysis was conducted through data reduction, data display, and conclusion drawing. The findings reveal that the University of Riau Reservoir functions not only as a water catchment area and environmental support facility but also as an informal social space utilized for various activities, including group discussions, social gatherings, sports, fishing, photography, and recreation. The comfortable, open, and natural environment of the reservoir encourages social interaction and strengthens relationships between students and local communities. However, environmental awareness among visitors remains varied, as evidenced by the presence of litter in several areas. The study concludes that the reservoir serves both social and ecological functions that are closely interconnected. Therefore, sustainable management is necessary to maintain environmental quality while supporting social activities within the campus and surrounding community.